Cholinesterase's Enzymes Inhibition and Michaelis-Menten Kinetics Studies on Ethnomedicinally Important Plant Chenopodium botrys - Iqbal, Naveed; Ullah, Farhat; Sadiq, Abdul; Shahid, Muhammad; Ayaz, Muhammad (Journal of Food Health and Bioenvironmental Science, 2023)
Chenopodium botrys (C. botrys) methanolic extract (Cb.Cr) and subsequent fractions were screened for inhibitory potentials against cholinesterase's. Acetylcholinesterase (AChE) and butyryl-cholinesterase (BChE) in vitro inhibitory potentials were evaluated employing Ellman's assay. Lineweaver-Burk a plot (1/v versus 1/[s]) in which v is the velocity of reaction and [s] is substrate concentration was sketched by Michaelis-Menten kinetics. In AChE inhibition assay, chloroform (Cb.Chf), ethyl acetate (Cb.EtAc) and crude extract (Cb.Cr) showed highest activity with 80.12±1.97, 71.79±0.67 and 69.00±1.52% inhibitions at concentration of 1 mg/mL with IC50 values of 50, 115 and 130 μg/mL, respectively. Similarly, Cb.Chf, Cb.EtAc and Cb.Cr showed the strongest activity against BChE causing 76.20±0.28, 70.48±0.19 and 62.75±1.79% inhibitions at 1 mg/mL with IC50 of 25, 55 and 195 μg/mL, respectively. For the AChE inhibition, the Vmax and Km values were noted as 70.08 μg/min and 55.21 μg/mL intended for Cb-Cr, 54.38 μg/min and 107.6 μg/mL for Cb-Hex, 82.65 μg/min and 51.09 μg/mL for Cb-Chf, 72.83 μg/min and 63.05 μg/mL for Cb-EtAt, and 64.4 μg/min and 82.27 μg/mL for Cb-Aq. likewise, the Vmax and Km values for BChE also displayed effective inhibitory potential of Cb-Cr (63.51 μg/min and 51.82 μg/mL), Cb-Hex (53.13 μg/min and 47.71 μg/mL), Cb-Chf (77.37 μg/min and 33.13 μg/mL), Cb-EtAc (72.28 μg/min and 37.84 μg/ mL), and Cb-Aq (59.18 μg/min and 34.67 μg/mL), respectively. In conclusion, C. botrys contains bioactive components which can be effective in the curing of Alzheimer's disease (AD) and other stress associated diseases.